Adaptation of emotional flexibility scale: Its association with subjective well being and resilience during covid-19 pandemic - ÜMMET, DURMUŞ (My University, 2022)
The corona virus (COVID-19) pandemic has led to a global health crisis causing fear and negative psychological consequences. In this study, the validity and reliability of the Emotional Flexibility Scale were evaluated in a sample of adolescents in Turkey. A total of 833 high school students from 65 different cities participated in the study. Emotional flexibility, adolescent psychological resilience, and adolescents\" subjective well-being Scales were used as data collection tools. For the adaptation of emotional flexibility scale, confirmatory factor analysis, convergent validity, and reliability analyses were used. Also, the mediating role of subjective well-being on the relationship between emotional flexibility and resilience was tested. Emotional flexibility was found to be associated with subjective well-being and resilience. The results of the study show that the Emotional Flexibility Scale is a valid and reliable measurement tool in the sample of adolescents in Turkey.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; SOSYAL BİLİMLER, İNTERDİSİPLİNER; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); SOCIAL SCIENCES, INTERDISCIPLINARY; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Sosyal Bilimler (çeşitli); Genel Sosyal Bilimler; Teknoloji ve İnovasyon Yönetimi; Yönetim Bilgi Sistemi; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences (miscellaneous); General Social Sciences; Management of Technology and Innovation; Management Information Systems; Social Sciences & Humanities; Adolescents; COVID-19; Emotional flexibility; Adaptation; Resilience; Subjective well-being; INDEXES; LIFE